2010
DOI: 10.1016/j.addbeh.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence, cigarette consumption and advice received from physicians: Change between 1996 and 2006 in Geneva, Switzerland

Abstract: a b s t r a c t a r t i c l e i n f o (29.2% in 1996, 32.1% in 2006, p = 0.52), but more smokers reported that they intended to quit in the next 6 months in 2006 (39.6%) than in 1996 (29.1%, p = 0.045). The association between smoking prevalence and income was stronger in 2006 (chi 2 = 53.7, p < 0.001) than in 1996 (chi 2 = 10.9, p = 0.012). In 2006 (no change since 1996), few smokers reported that, during their last medical visit, their physician told them to quit smoking (27.3%) or offered them help to quit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
3
15
1
1
Order By: Relevance
“…Thus, most participants answered during the weeks when craving and withdrawal symptoms are the most intense. The patterns of e-cigarette use in this study were comparable to patterns observed in previous studies of vapers: 120 puffs/day (Etter and Bullen, 2011b); 175 puffs/day (Etter, 2010a); 200 puffs/day (Etter and Bullen, 2011c;Foulds et al, 2011); 235 puffs/day (Dawkins et al, 2013b); 4 ml e-liquid per day (Farsalinos et al, 2013a). This suggests that participants in this study were not particularly intensive users and that our results are generalizable to most daily vapers.…”
Section: Strengths and Limitationssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, most participants answered during the weeks when craving and withdrawal symptoms are the most intense. The patterns of e-cigarette use in this study were comparable to patterns observed in previous studies of vapers: 120 puffs/day (Etter and Bullen, 2011b); 175 puffs/day (Etter, 2010a); 200 puffs/day (Etter and Bullen, 2011c;Foulds et al, 2011); 235 puffs/day (Dawkins et al, 2013b); 4 ml e-liquid per day (Farsalinos et al, 2013a). This suggests that participants in this study were not particularly intensive users and that our results are generalizable to most daily vapers.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…Nevertheless, it is possible that some respondents gave the answers that they thought might help defend their position (e.g., by reporting more effects on craving and on smoking cessation). When they were smokers, participants were more dependent on tobacco than smokers in the general population (Etter, 2010b). Thus, our results may have limited generalizability and should be interpreted with caution.…”
Section: Strengths and Limitationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared with representative samples of the general population, this sample also included more women and heavier smokers (Etter, 2010;Etter and Perneger, 2001), which may determine the generalizability of this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In Italy, the overall prevalence of smoking among hospital staff is 30.6% and among physicians is 21.2%; moreover, only 58.7% of hospital health staff tackles the issue of smoking in any contact with patients [9]. In Switzerland, smokers did not receive additional advice to quit or help to quit smoking by their physicians over a period of 10 yrs [10].…”
mentioning
confidence: 99%